A novel loss-of-function mutation in the GNS gene causes Sanfilippo syndrome type D - (:unkn) unknown (My University, 2009)
A novel loss-of-function mutation in the GNS gene causes Sanfilippo syndrome type D: Mucopolysaccharidosis type IIID (MIM 252940) is the least common form of the four subtypes of Sanfilippo syndrome. It is an autosomal recessive lysosomal disorder caused by a deficiency of the N-acetylglucosamine-6-sulphatase (GlcNAc-6S sulphatase, GNS), a hydrolase, which is one of the enzymes involved in heparan sulfate catabolism leading to lysosomal storage. The clinical features of this disorder are progressive neurodegeneration with relatively mild somatic symptoms. Twenty patients have been described in the literature and only seven causative mutations in the GNS gene encoding GlcNAc-6S sulphatase have been reported to date. We present the clinical and molecular results of a newly diagnosed Turkish patient with MPS IIID. We identified the novel homozygous single base pair insertion, c.1226GinsG, which leads to a frame-shift and a premature truncation of the GNS protein (p.R409Rfs21X). CONCLUSION: This novel mutation provides further evidence that loss-of-function is the underlying pathophysiological mechanism of this rare phenotype.
Keywords: Humans; Turkey; Male; Child; Alleles; Phenotype; Disease Progression; Genes, Recessive; Chromosome Aberrations; Intellectual Disability; DNA Mutational Analysis; Deafness; Base Pairing; Frameshift Mutation; Genetic Counseling; Mucopolysaccharidosis III; Mutagenesis, Insertional; Sulfatases